Rare finding of a large cell poorly differentiated neuroendocrine tumor in the colon - Luster, Stephanie A.; Kakish, Daniel K.; Gill, Manroop; Kumthekar, Narendra (International Surgery Journal, 2020)
A 43 year old female presented to the emergency department for nausea, vomiting and abdominal pain secondary to a bowel obstruction subsequently revealed to be a poorly differentiated large cell neuroendocrine tumor of the colon. After a CT scan showed a mass in the ascending colon with possible metastasis to the right lobe of the liver, an exploratory laparotomy was performed. A hemicolectomy was performed with biopsy of the liver mass. Pathology was consistent with large cell neuroendocrine tumor in all specimens including the liver biopsy, ascending colon, and transverse colon. Although large cell neuroendocrine tumors of the colon are a rare malignancy, they are an important consideration in the workup of multiple colonic masses with metastases, especially in patients presenting with bowel obstruction. The literature on poorly differentiated large cell neuroendocrine cancer and treatment is reviewed. Poorly differentiated large cell neuroendocrine tumor is a rare pathology but should be included in the differential diagnosis in patients presenting with a colon mass and bowel obstruction.